Parental Cooperation In Inclusion Of Hearing Impaired Children In Inclusive Education - B. Q. Subanova (Genius Journals, 2024)
A child grows up in a family, and from the first years of his life, he learns from the family everything that is characteristic of the family, good and bad, and learns social norms, norms of relationships between people. The family is the source and intermediary link in the transfer of social and historical experience to the child, primarily in the experience of emotional and business relationships between people. Taking this into account, we can rightly assume that the family was and will be the most important institution for raising and socializing a child in a healthy peer environment.
Keywords: environment; historical; years; family